Praktik Cyber Begging dalam Perspektif Surah Al-Baqarah Ayat 273 - Azizah, Dinda Nur; Muhammad Hidayat (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The phenomenon of cyber begging is a digital social practice that utilizes public empathy through social media. This research aims to analyze the phenomenon based on the interpretation of QS. Al-Baqarah/2:273, and examine it from the perspective of social-digital literacy. The method used is a descriptive qualitative approach through literature study and thematic interpretation analysis. The results show that the practice of cyber begging contradicts the principle of al-'iffah (maintaining self-respect) as outlined in the Quran. In addition, this phenomenon often blurs the line between solidarity and exploitation of public empathy. Therefore, Islamic value-based digital literacy education is needed to build a digitally smart and ethical society.